Media and monotheism: presence, representation, and abstraction in ancient Judah - Schaper, Joachim (Orientalische Religionen in der Antike, 2019)
Cover -- Titel -- Preface -- Acknowledgments -- Table of Contents -- Abbreviations -- Introduction -- Chapter 1: Images, Writing and Money: Three Media and the Rise of Monotheism -- 1.1 The Visual, the Textual, and the Numerical in the Earliest Notation-Systems -- 1.2 The Earliest Alphabets and the Changing Constellation of the Visual, the Textual, and the Numerical -- 1.3 The Development of Writing in the Context of the Division of Labour -- 1.4 Presence, Representation, and Abstraction in Ancient Religions -- 1.41 Presence and Representation in (the Study of) Religion -- 1.411 Spoken Language and Written Texts: 'Orality and Literacy' and the 'Technology of Writing' -- 1.412 Writing and Images, Verbal and Visual Representation, and Abstraction -- 1.413 Money, Representation, and Abstraction -- 1.5 Media and Monotheism -- 1.51 What Is a Medium? -- 1.52 What Is Monotheism? -- 1.521 'Monotheism', Its Detractors, and the Question of Other 'Monotheisms' Influencing the Development of the Yahweh Religion -- 1.53 The Structure of the Present Study -- Chapter 2: The Word-Image Dialectic and the 'Production of Presence' -- 2.1 Conceptualisations of Divine Presence in Mesopotamia and in Greece -- 2.2 Early Conceptualisations of Divine Presence in Israel and in Pre-Exilic Judah: Judges 17-18 -- 2.3 The Problem of Aniconism -- 2.4 Prophecy and the Word-Image Dialectic -- 2.41 Hosea -- 2.42 Deutero-Isaiah -- 2.421 The Terminology Used in the Anti-Idol Polemics of Isaiah 40-55 -- 2.422 Anti-Idol Polemics in Isaiah 40-55 - a Dialogue with Genesis 1:26-27, Interpreted against the Background of Deuteronomy 4 -- 2.423 Anti-Idol Polemics and Monotheism -- 2.43 Jeremiah -- 2.44 Ezekiel -- 2.5 The Word-Image Dialectic in the Hexateuch -- 2.51 Genesis 1:26-27 -- 2.52 Exodus: the Acousmatic Voice, Writing, and Images -- 2.521 Media in the Book of Exodus: Voices.